An Interpretation of Controversial Points in Keynes’s General Theory - Possas, Mario Luiz (Brazilian Keynesian Review, 2015)
The paper offers an interpretation of the General Theory based on two main assumptions: (i) that its core is heterodox (meaning far from Neoclassical references) and (ii) that, while not working out a dynamic model, it is neither static nor based on the notion of equilibrium in the usual sense, i.e. as an attractor. It amounts rather to a foreword to a dynamic theory, given its emphasis on (future) time and expectations. The exposition is centered on the division between short and long run (period) with corresponding particularities and distinctions. In the first case, a more general concept of the principle of effective demand is proposed, from which the relation investment/savings, supply and demand functions at the Micro level – where basic variables are determined -, the “point of effective demand” and corresponding aggregative versions are interpreted. In the second case, investment decisions are examined on the light of chap. 17, concerning investment in capital assets, i.e. individual demand for assets. The central concept of uncertainty is introduced here, giving place to money as an asset as well as to liquidity preference and the rate of interest theories. Long term expectations under uncertainty give rise to other two key concepts – the state of confidence and the convention. As a result, his peculiar and crucial notion of instability of investment follows, as well as its extension to the capitalist economy as a whole.